Biochemical Study of Blood Serum and Seminal Plasma of Patients with Oligospermia - Ghayth Sinan M. Agha; Saba Zeki M. Al-Abachi; Mohammed R. Khedhr3 (African Journal of Advanced Pure and Applied Sciences, 2023)
The study began in September 2021 and was extended in September 2021 and extended until May 2022. (172) samples of blood serum and (70) samples of seminal plasma were collected after instructing the patient. Abstain from sexual intercourse for 3 consecutive days. Samples were obtained from Al-Salam Teaching Hospital and specialized laboratories in Mosul city. Samples were divided into two groups: A control group and Oligospermia patients were diagnosed by specialized doctors. The samples were classified between the groups based on the general semen analysis by CASA device. The study included measuring the biochemical parameters of serum and seminal plasma for both control and patients groups, which included: estimating the concentrations of vitamins C, E, and D, measuring glutathione (GSH) and malondialdehyde (MDA), measuring some salts and minerals such as calcium (Ca), sodium (Na), potassium(K), and chloride (Cl), as well as measuring the concentrations of some trace elements such as copper (Cu), zinc (Zn), and cobalt (Co), and estimating some proteins such as prostate-specific antigen (PSA), albumin and total protein concentrations. The study showed that there were significant decrease in the concentration of vitamins C, E, D, and in Zn and GSH concentrations; we noted a significant increase in the concentration of MDA, and in PSA concentration in blood serum of patients group compared to the control group. It was also shown on seminal plasma that there was a significant decrease in the concentration of Na, K, Ca and albumin, while there was a significant increase in Cu, Co and in the concentration of total protein of oligospermia patients compared to control group.